HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF DI PUSKESMAS LIRUNG KECAMATAN LIRUNG KABUPATEN KEPULAUAN TALAUD - Maga, Nadila (Journal Of Community & Emergency, 2024)
Exclusive breastfeeding is mother’s milk that is given to her child immediately after birth until the age of six months without any additional food or drink. Family support is the most important part that has a very big influence on the success of exclusive breastfeeding.This study used an analytic survey with a cross sectional approach with a sample of 40 respondents taken using total sampling. Based on the research conducted, it shows that 57,5% ( 23 respondents ) Have not received family support in providing exclusive breastfeeding. And mothers who get family support from the family for exclusive breastfeeding, namely 42,5% (17 respondents). Then based on the results of statistical analysis obtained p value = 0,000 which is smaller than a (0,05), then Ho is rejected and Ha is accepted. The conclusions from the results of this study indicate that there is a “ Relationship Between Family Support And Exclusive Breastfeeding In The Lirung District, Talaud Archipelago District.